Valproic acid-mediated transcriptional regulation of human GM3 synthase (hST3Gal V) in SK-N-BE(2)-C human neuroblastoma cells - Kwon Haw-young; Kang Nam-young; Dae Hyun-mi; Kim Kyoung-sook; Kim Cheorl-ho; Do Su-il; Lee Young-choon (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether valproic acid (VPA) modulates human GM3 synthase (hST3Gal V) mRNA expression, as a part of ganglioside GM3 biosynthesis, in human neuroblastoma cells. Methods: Using RT-PCR and immunofluo-rescent confocal microscopy, we examined hST3Gal V mRNA and GM3 levels during VPA-induced differentiation of human neuroblastoma SK-N-BE(2)-C cells. We characterized the VPA-inducible promoter region within the hST3-Gal V gene using luciferase constructs carrying 5′-deletions of the hST3Gal V promoter. Results: RT-PCR indicated that VPA-mediated hST3Gal V induction is transcriptionally regulated. Functional analysis of the 5′-flanking region of the hST3Gal V gene demonstrated that the -177 to -83 region, which contains a cAMP-responsive element (CRE) at -143, functions as the VPA-inducible promoter by actively binding CRE binding protein (CREB). In addition, site-directed mutagenesis and electrophoretic mobility shift assay indicated that the CRE at -143 is crucial for the VPA-induced expression of hST3Gal V in SK-N-BE(2)-C cells. Conclusion: Our results isolated the core promoter region in the hST3Gal V promoter, a CRE at -143, and demonstrated that it is essential for transcriptional activation of hST3Gal V in VPA-induced SK-N-BE(2)-C cells. Subsequent CREB binding to this CRE mediates VPA-dependent upregulation of hST3Gal V gene expression.